Silat Pengantin: Seni Pertunjukan Tradisi Melayu di Bentan Penao, Kepulauan Riau - Widyanarto, Widyanarto; Hendra, Doni Febri; Aprinnostein, Siguti (LP2M ISBI Bandung, 2019)
ABSTRACTThe wedding martial in Riau Islands Province is a traditional Pencak Silat that is part of Malay cultures. The University of Kiambang Putih in Bentan Penao, Bintan regency, martial arts performance presented at traditional Malay wedding is also called Silat flag. The form of presentation is divided into two parts, namely silat flag and silat performance. Silat flag is displayed by two fighters, using the red flag and white color properties. The red and white flag are symbolized to unite two human beings into the family ark. The red flag is interpreted as red blood, which is from the bride. The symbol of the white flag is interpreted as white blood, which is from the groom. The Silat flag performance ends with the unification of both flags. It will be continued with silat performance. The Silat performance is displayed by one fighter who performed in turn. The bridal Silat show is accompanied by musical accompaniment consisting of instruments of two martial arts and gongs. The pattern of playing his musical instruments is played repeatedly, monotonically, and his apparent sanctity.Keywords: Bride Silat, Traditional Art Performances, Malay CustomsABSTRAKSilat pengantin di Provinsi kepulauan Riau merupakan seni pencak silat tradisional yang menjadi bagian budaya Melayu.Perguruan Kiambang Putih di Bentan Penao, kabupaten Bintan, pertunjukan seni silat yang disajikan di acara pernikahan adat melayu ini disebut juga dengan istilah silat bendera.Bentuk penyajiannya terbagi menjadi dua bagian, yaitu silat bendera dan silat persembahan.Silat bendera ditampilkan oleh dua orang pesilat, dengan menggunakan properti bendera warna merah dan warna putih.Simbol bendera berwarna merah dan putih memiliki makna untuk mempersatukan dua insan manusia ke dalam bahtera keluarga.Bendera merah dimaknai sebagai darah merah, dalam hal ini dari mempelai wanita.Simbol bendera putih dimaknai sebagai darah putih, dalam hal ini dari mempelai pria.Persembahan Silat bendera diakhiri dengan menyatunya kedua bendera.Dilanjutkan dengan silat persembahan.Silat persembahan ditampilkan oleh satu orang pesilat yang dilakukan secara bergantian.Pertunjukan silat pengantin diiringi oleh musik pengiring yang terdiri dari instrumen dua buah gendang silat dan gong.Pola memainkan instrumen musiknya dimainkan secara berulang-ulang, monoton, dan tampak kesakralannya.Kata Kunci: Silat Pengantin, Pertunjukan Seni tradisi, Adat Melayu ?